Efeito do tratamento térmico do titânio sobre a proliferação de células pré-osteoblásticas - Macedo, Haroldo Reis Alves de (2008)
Titanium is a biomaterial widely employed in biomedical applications (implants, prostheses, valves, stents). Several heat treatments are usually used in order to obtain physical properties required to different applications. This work studied the influence of the heat treatment on microstructure of commercial pure titanium, and their consequences in growth and proliferation of MC3T3-E1 cells. Discs of titanium were treated in different temperatures, and characterized by optical microscopy, image analysis, wettabillity, roughness, hardness and X-ray diffraction. After the heat treatment, significant modifications in these properties were observed. Pattern images of titanium, before and after the cell culture, were compared by overlapping to analyze the influence of microstructure in microstructure and preferences guidance cells. However, in general, titanium discs that showed a higher residual strength also presented an increase of cells numbers on surface